Formulation and evaluation of micro-bound larval feed for Macrobrachium rosenbergii (de Man) - Hari, B; Kurup, B Madhusoodana (Indian Journal of Fisheries, 2011)
The efficacy of three dry micro-bound hatchery feeds (squid feed – SF, prawn feed -PF and squid-prawn feed - SPF) were evaluated in the larval rearing of Macrobrachium rosenbergii with newly hatched Artemia nauplii and prawnegg custard. They were tested in different feeding protocols – T1 (prawn-egg custard + Artemia), T2 (Artemia + SPF), T3 (Artemia + PF), T4 (Artemia + SF) and T5 (SPF only). Newly hatched Artemia nauplii served as the control (C). Higher survival rate was recorded in T2 (10.55%), followed by T4 (9.03%) and T3 (8.25 %), whereas it was in a lower side in control (2.44%) and T1 (2.24%). Micro-bound larval feed without Artemia combination (T5) does not support life after 4th larval stage. Lower post larval (PL) scout time was recorded in T4 followed T2 (on 23rd and 25th days respectively). Lowest 95% PL drop time was recorded in T2 (37th day) followed by T4 (38th day), C and T3 (39th day). The results of the present study showed that it is possible to minimise the use of Artemia nauplii in the larval rearing of M. rosenbergii by incorporating microbound diets in feeding protocols. Besides, the study revealed the importance of live feeds in the nutrition of early larval stages of M. rosenbergii.